Effects of Guizhi decoction for diabetic cardiac autonomic neuropathy: A protocol for a systematic review and meta-analysis - Chen, Junmin (Medicine (Baltimore), 2020)
BACKGROUND: Diabetic cardiac autonomic neuropathy (DCAN) is one of the serious complications of diabetes. The pathogenesis of DCAN has not been fully elucidated. There is currently no effective treatment for such chronic disease. Traditional Chinese medicine has a long clinical history for the prevention and treatment of diabetes and chronic complications, and it also shows certain advantages in the treatment of DCAN. Many clinical studies have confirmed that Chinese medicine Guizhi decoction can reduce the clinical symptoms and improve neuronal function of patients with DCAN. So we intend to conduct a systematic review further clarified the effectiveness and safety of Guizhi decoction for DCAN. METHODS: We will search each database from the built-in until July 2020. The English literature mainly searches Cochrane Library, PubMed, EMBASE, and Web of Science, while the Chinese literature comes from CNKI, CBM, VIP, and Wangfang database. Simultaneously we will retrieval clinical registration tests and grey literatures. In this study, only the clinical randomized controlled trials (RCTs) were selected to evaluate the efficacy and safety of Guizhi decoction in the treatment of DCAN. The 2 researchers independently conducted literature selection, data extraction, and quality assessment. Statistical heterogeneity among studies will be evaluated using the Cochran Q test (x(2)) and the I(2) statistical value. We will utilize the Review Manage software V5.3.0 (The Nordic Cochrane Center, The Cochrane Collaboration, 2014, Copenhagen, Denmark) to statistically analyze all data. ETHICS AND DISSEMINATION: This study is a protocol for a systematic review of Guizhi decoction as a treatment of DCAN patients. RESULTS: This study will provide high-quality synthesis of effectiveness and safety of Guizhi decoction for DCAN. CONCLUSION: This systematic review aims to provide new options for Guizhi decoction treatment of DCAN in terms of its efficacy and safety. REGISTRATION NUMBER: INPLASY202080018.